SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMK TARUNA BANGSA BEKASI - Fajar Agustini; Linda Marlinda; Luci Kanti Rahayu (Jurnal Sistem Informasi, 2014)
Abstract— Academic activities is a process where the educational activities that do require information on their activities quickly. But in fact not a few obstacles that occur. This is because often there is accumulation of student data and student data made it difficult to search if any time the data was required, it takes a long time in making a report student data, registration of students into the academic value of students' academic and book value into the report cards and also make the report academic students should be left to the head of school, time constraints of parents so that information about the academic is not obtained quickly, the lack of a media campaign that led to the lack of academic information obtained by the parents and students, the unavailability of other media in recording the student's academic so that parents or students in knowing the information students need to wait for thedistribution of report cards, through research is expected to build a computer-based academic information system that can minimize the disadvantages that occur so as to meet the information needs for teachers, students to the wider community.